2017
DOI: 10.1371/journal.pone.0180071
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of screening and confirmatory test results for HIV in Xi’an, China

Abstract: ObjectivesIndividuals with recent or acute HIV infection are more infectious than those with established infection. Our objective was to analyze the characteristics of detection among HIV infections in Xi'an.MethodsA 4th-generation kit (Architect HIV Ag/Ab Combo) and three 3rd-generationEIA kits (WanTai, XinChuang and Livzon) were used for HIV screening. Overall, 665 individuals were identified as positive and were tested by western blotting (WB). The characteristics of the screening and confirmatory tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, of the 217 repeatedly reactive cases by the assay, 46.08% were found to be FP. We found that the FP rate decreased as the test values increased [14, 33]. For ARCHITECT HIV Ag/Ab Combo, the FP rate was 100% at 1–10 of COI, but the FP rate decreased to 0 when the COI was ≥30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, of the 217 repeatedly reactive cases by the assay, 46.08% were found to be FP. We found that the FP rate decreased as the test values increased [14, 33]. For ARCHITECT HIV Ag/Ab Combo, the FP rate was 100% at 1–10 of COI, but the FP rate decreased to 0 when the COI was ≥30.…”
Section: Discussionmentioning
confidence: 99%
“…New and recent HIV infections are more infectious than chronic infections [1114], thus early identification of HIV infection is crucial to prevent HIV transmission [15]. The algorithm requires a sequence of tests to identify HIV infection for the repeatedly reactive subjects.…”
Section: Introductionmentioning
confidence: 99%
“…However, for cases with low COI values (e.g., COI = 1.0–15.0), most were false-positive, and a few had early HIV infections. It is difficult to distinguish false-positives and early HIV infections using western blotting because false-positives may also show positivity for the P24 antigen or other single antibody band caused by crossreaction; the patient must be followed up for 1, 3, or even 6 months to reconfirm the results 6 , 8 , and this can waste a lot of manpower, materials, and financial resources. Moreover, there may be a delay in the diagnosis and treatment of the patient, which could cause a heavy psychological burden to the patient 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies show that there was an association between test values and subsequent confirmatory results. As COI values increased, the number of FP decreased, and the possibility of positive results was higher [13,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies show that there was an association between test values and subsequent confirmatory results. As COI values increased, the number of FP decreased, and the possibility of positive results was higher [ 13 , 26 , 27 ]. Thus, the present study was carried out to evaluate the performance of Elecsys® HIV combi PT assay in a large cohort of patients from 2018 to 2019 in Nanjing, a low-HIV-prevalence region of East China, to analyze the sensitivity, specificity, and positive predictive value (PPV) at different COI, and to seek for an optimal cutoff that can predict HIV infection at early period.…”
Section: Introductionmentioning
confidence: 99%